2022
DOI: 10.2174/1573399817666210617154535
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Phytotherapy Used in the Management of Type II Diabetes

Abstract: : Diabetes mellitus is related to unconstrained high blood sugar, and it is linked with long-term impairment, dysfunction, and failure of several organs. Since 1980, the global frequency of diabetes has almost doubled in the adult population. In very rare cases of poor prevention and management programs, diabetes will cause the deteriorated effects on the health and lifespan of the world population, and so on the world economy. Supplements, however, help in the improvement of nutritional deficiencies. Phytothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
1
0
4
Order By: Relevance
“…Na Odontologia, a valorização, aceitação e a aplicação da fitoterapia têm sido perceptíveis, uma vez que esta ciência tem demonstrado resultados promissores, apresenta baixo custo, fácil acessibilidade, biocompatibilidade e menor probabilidade de causar efeitos colaterais (Enioutina et al, 2017;Jahangir et al, 2020;Sharma et al, 2021). avaliaram por seis meses a ação de um medicamento à base de plantas medicinais, obtendo eficácia em várias lesões, além de observarem redução da intensidade dolorosa e da taxa de ocorrência em comparação ao grupo controle.…”
Section: Fitoterapia Na Odontologiaunclassified
“…Na Odontologia, a valorização, aceitação e a aplicação da fitoterapia têm sido perceptíveis, uma vez que esta ciência tem demonstrado resultados promissores, apresenta baixo custo, fácil acessibilidade, biocompatibilidade e menor probabilidade de causar efeitos colaterais (Enioutina et al, 2017;Jahangir et al, 2020;Sharma et al, 2021). avaliaram por seis meses a ação de um medicamento à base de plantas medicinais, obtendo eficácia em várias lesões, além de observarem redução da intensidade dolorosa e da taxa de ocorrência em comparação ao grupo controle.…”
Section: Fitoterapia Na Odontologiaunclassified
“…It has been demonstrated that a range of medicinal plants and fruit-and vegetablebased foods can intervene at critical stages of glucose metabolism and could potentially be used to develop new anti-diabetic medications [9,10]. There are multiple mechanisms underlying their anti-diabetic effects, including intervening with the insulin receptor signaling pathways, the translocation of GLUT4 receptors, the activation of PPAR-γ, or the reduction of intestinal glucose absorption [11]. For centuries, essential oils (EOs) have been employed for medicinal and traditional practices.…”
Section: Introductionmentioning
confidence: 99%
“…Uma abordagem interessante é explorar as inúmeras propriedades das plantas medicinais. A valorização, aceitação e o emprego da fitoterapia na odontologia tem sido notório pois apresenta baixo custo, fácil acesso, biocompatibilidade e principalmente tem apresentado resultados promissores (Enioutina et al, 2017;Jahangir et al, 2020;Sharma et al, 2021).…”
Section: Introductionunclassified